The Implementation of Task-Based Learning to Improve Reading Comprehension of the Second-Year Students’ of SMP Negeri 1 Sungguminasa - Sukardi, Vera; Dollah, Syarifuddin; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
The purpose of this study was to find out whether the use of Task-Based Learning can improve students reading comprehension of the second-year students of SMP Negeri 1 Sungguminasa. This research was conducted at SMP Negeri 1 Sungguminasa. The researchers used a quantitative research method. The population of this research is the second-year students of SMP Negeri 1 Sungguminasa. The instrument in this study was reading tests. The tests were given before the treatment (pre-test) and after the treatment (post-test). Based on the result of the mean score, the researchers found that the use of Task-Based Learning could improve the student's reading comprehension skills. It was proven by the result of the post-test which was higher than the result of the pre-test (86.28 > 39.63). Therefore, the researchers concluded that the use of Task-Based Learning can improve second-year students' reading comprehension skills at SMP Negeri 1 Sungguminasa.